Incidental Trifid Median Nerve Unveiled in a Lactating Mother - Md. Abu B. Siddiq; M Tanveer Hossain Parash (Cureus, Inc., 2019)
Several anatomical variations concerning the median nerve have surfaced in the medical literature. Among them, bifid median nerve or median nerve bifurcation with or without persistent median artery has been widely reported. Sporadic case reports describe median nerve trifurcation (trifid median nerve) as well. In the present report, we describe carpal tunnel syndrome manifestations in association with trifid median nerve unveiled incidentally under high-frequency musculoskeletal ultrasonogram in a lactating mother-a first in the medical literature.